DETERMINACIÓN DE COMPUESTOS BIOACTIVOS DEL AGUAYMANTO (Physalis peruviana, Linnaeus, 1753) Y DE SU CONSERVA EN ALMÍBAR MAXIMIZANDO LA RETENCIÓN DE ÁCIDO ASCÓRBICO - Encina Zelada y Cols., Christian Rene (2019)
The present investigation is the result of the study of the bioactive compounds present in the aguaymanto (Physalis peruviana) from the valley of Mantaro-Peru and its canned in syrup. In Stage I were determined the bioactive compounds in the raw material, correspondents to maturity‟s condition 2 and 3 as [1] was of 28,55 mg of ascorbic acid /100 g; 1,77 mg of β-caroten/100g; 79,23 mg clorogenic acid /100 g and antioxidant capacity its divides in hidrofílic (288,95 µg eq trolox/g) and lipofílic (297,51µg eq trolox/g), measured by the ABTS method and of 249,23 µg eq trolox/g measured by the method of the DPPH. In Stage II were decided the factors and its levels that influenced significantly (p<0,05) in the retention of the ascorbic acid in the process of production of aguaymanto canned in syrup using Taguchi´s method. The pH of the syrup and the temperature of the heat treatment turned out to be the factors of major influence in the retention of the ascorbic acid. The levels with which major quantity of ascorbic acid was retained were: wax-off time (90 s), wax-off temperature (80°C), pH of the Syrup (2,5), degrees Brix of the Syrup (30), wax-off concentration (0,05 %), temperature (95°C) and time (11,52 min) of the heat treatment. In Stage III was characterized physicist, chemically and microbiologically corresponding to the process of production of the aguaymanto canned in syrup realized with the parameters that maximized the retention of ascorbic acid (50,54%), determining in addition the effect of the technological treatment on the content of totally caroten (1,59 mg of •-caroteno/100g), Compounds Fenólicos (39,23 mg ác. Clorogénico/100 g) and antioxidant capacity (383,73 µg eq trolox/g and 132,12 µg eq trolox/g measured by the methods of the ABTS and DPPH respectively).